Distribution of polyglutamine proteins in Purkinje cells of the human and rat cerebellum - Gilerovich, E. G.; Grigorev, I. P.; Alekseeva, O. S.; Kirik, O. V.; Korzhevskii, D. E. (Journal of evolutionary biochemistry and physiology, 2017)
In this work, localization of poly-glutamine proteins in the cerebellum is studied in human and rats, with the latter being a standard experimental organism for modeling brain pathologies